JOINT STATEMENT INDONESIA-CHINA: ANALISA DAMPAK KERJA SAMA PADA BIDANG MARITIM TERHADAP KEDAULATAN NEGARA DI LAUT NATUNA UTARA - Naqiyyah, Isthiqosah Shalsa (Triwikrama: Jurnal Ilmu Sosial, 2024)
Indonesia and China have established diplomatic relations since 1950. The relationship continues and develops to this day. Both countries are involved in various agreements and cooperation. On November 9, 2024, Indonesian President Prabowo Subianto together with Chinese President Xi Jinping agreed to a Joint Statement or cooperation in the maritime sector. However, this cooperation has become a controversial issue because of the pros and cons from various parties who consider this cooperation to threaten the country’s sovereignty over the North Natuna Sea area which is a disputed area between Indonesia and China. This study aims to analyze the impact of the Joint Statement on the country’s sovereignty in the North Natuna Sea. The method used in this study is a qualitative approach with secondary data (articles, news, and books) as the main data source. This study found that there are positive and negative impacts of the Indonesia-China cooperation. On the one hand, this cooperation can strengthen diplomatic relations and improve the economy of the two countries. However, this cooperation can also pose a threat to Indonesia’s sovereignty, especially in the North Natuna Sea area which is Indonesia’s EEZ (Exclusive Economic Zone).